Arbeitsrechtliche Schwellenwerte und betriebliche Arbeitsplatzdynamik: eine empirische Untersuchung am Beispiel des Schwerbehindertengesetzes - Lena Koller; Claus Schnabel; Joachim Wagner (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2006)
– This paper makes an empirical investigation of the effects of the German Disabled Persons Act on employment dynamics using data from the Federal Employment Agency and the IAB Establishment Panel. The data permit an investigation of the second threshold of this law, which in the observation period 1999/2000 required that firms with more than 25 employees employ two disabled persons or pay a penalty. Descriptive and multivariate analyses indicate that employment growth is slightly dampened if firms are just below this threshold and do not have enough disabled employees (i.e. would have to pay a penalty when crossing this threshold). There is no indication, however, that firms in a similar situation above the threshold reduce employment more intensively in order to fall below the threshold and thus avoid paying the penalty.
Keywords: 330; Schwerbehindertengesetz - Auswirkungen; Arbeitsplatzangebot; Beschäftigungspflicht; Ausgleichsabgabe; Arbeitskräftenachfrage; Beschäftigungseffekte; IAB-Betriebspanel; Schwellenwert